2023
DOI: 10.3390/signals4020017
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Communication System Based on Wireless LPWAN and SD-WAN Technologies: A Hybrid Approach

Abstract: Emergency Communication Systems (ECS) are network-based systems that may enable people to exchange information during crises and physical disasters when basic communication options have collapsed. They may be used to restore communication in off-grid areas or even when normal telecommunication networks have failed. These systems may use technologies such as Low-Power Wide-Area(LPWAN) and Software-Defined Wide Area Networks (SD-WAN), which can be specialized as software applications and Internet of Things (IoT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The incorporation of technology into emergency response systems is important, and the IoT holds significant potential for supplying sensitive information during rescue and relief efforts in the event of natural disasters. While the LPWAN has been successfully integrated into various intelligent environments like smart buildings, banks, agriculture, smart vehicles, traffic management, smart cities, healthcare, and sensitive infrastructure [ 5 , 8 , 9 , 12 , 13 , 14 ], its implementation has not been geared toward providing LPWAN-based emergency response systems for individuals with special needs on a smart campus. Furthermore, ad hoc networks have not been utilized to reduce the latency and enhance the reliability.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of technology into emergency response systems is important, and the IoT holds significant potential for supplying sensitive information during rescue and relief efforts in the event of natural disasters. While the LPWAN has been successfully integrated into various intelligent environments like smart buildings, banks, agriculture, smart vehicles, traffic management, smart cities, healthcare, and sensitive infrastructure [ 5 , 8 , 9 , 12 , 13 , 14 ], its implementation has not been geared toward providing LPWAN-based emergency response systems for individuals with special needs on a smart campus. Furthermore, ad hoc networks have not been utilized to reduce the latency and enhance the reliability.…”
Section: Related Workmentioning
confidence: 99%
“…This transformation has led to the development of cost-effective networks with the capacity to cover large areas. One such network is the Long-Range (LoRa) network, which belongs to the family of low-power wide-area networks (LPWANs) [ 5 , 6 ]. These cutting-edge technologies allow for the placement and maintenance of sensors using a low-power wide-area client, with a maximum range of 30 km in sensor network operational areas [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Figure 1 [ 5 ], we have found that current trends and future trends both show that wide area protocols and short-range protocols-supported devices are mainly used while cellular protocols-supported devices are comparatively less in use. Considerable research [ 8 , 9 , 10 ] has supported the idea that for broad areas and long ranges, primarily industrial, scientific, and medical (ISM) band-based LPWAN protocols are superior to cellular IoT protocols. Three of the key requirements of IoT technologies are low power consumption and long-range communication at low cost [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%